The Wehrmacht's Last Stand : The German Campaigns of 1944 - 1945 - Citino, Robert Michael, 1958- (Book collections on Project MUSE., 2017)
"This third volume in Rob Citino's 'Wehrmacht trilogy' looks at the fight of the German Wehrmacht against the Allies from January 1944 to May 1945. One of the most pressing questions of World War II is: What kept the German army going in an increasingly hopeless situation? What kept the General Staff planning, the commanders commanding, and the soldiers fighting, even when the situation clearly seemed hopeless? Over the years, historians have posited various answers. Hitler seems the key reason that Germany fought on when most nations would have cracked. Other scholars point to the role of ideology and to National Socialist indoctrination as the heart of Germany's prolonged resistance. Rob Citino maintains the 'German way of war' led the German army to fight on to the bitter end. In a wider context it invites a reconsideration of why armies fight"--Provided by publisher.